2006
DOI: 10.1111/j.1365-2982.2006.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter gene polymorphism and irritable bowel syndrome

Abstract: Polymorphisms in the promoter region of the serotonin reuptake transporter (SERT) gene may underlie the disturbance in gut function in patients with irritable bowel syndrome (IBS). Association studies of SERT polymorphisms and IBS have shown diverse results among different countries, which might be due to racial and subject composition differences. The aim of this study was to assess the potential association between SERT polymorphisms and IBS in Koreans. A total of 190 IBS patients, who met the Rome II criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 24 publications
8
48
0
4
Order By: Relevance
“…Regarding the SERT polymorphism, the frequencies of the SERT ss genotype and s allele were higher in IBS patients that in healthy subjects. Our findings are in agreement with the study of Park et al [23]. The SERT gene encoding the SERT protein is located on chromosome 17q12.2-q1.…”
Section: Discussionsupporting
confidence: 96%
“…Regarding the SERT polymorphism, the frequencies of the SERT ss genotype and s allele were higher in IBS patients that in healthy subjects. Our findings are in agreement with the study of Park et al [23]. The SERT gene encoding the SERT protein is located on chromosome 17q12.2-q1.…”
Section: Discussionsupporting
confidence: 96%
“…However, there are other studies reporting a significant association between IBS-D and the S/S genotype. 34,35 An Indian study demonstrated that the frequency of SLC6A4 S/S genotype was higher in IBS-D than IBS-C, IBS-M and controls. 36 These genotypic results were different from our study, but taking the serotonin level and its association on subtypes into consideration, they might be in line with our study at least in part.…”
Section: Discussionmentioning
confidence: 99%
“…A Turkish study by Pata et al 9 reported an association of D-IBS with the l/s SERT-P genotype. In addition, the authors also described an 12 again found an association between the s/s SERT-P genotype and D-IBS. The results from these four recent genetic association studies are summarized in Fig.…”
Section: Sert Polymorphisms In Ibsmentioning
confidence: 81%